Effects of different processing methods on the quality characteristics of natural sweetener Stevia (stevia rebaudiana) - Evangelista, Oliver C.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT Stevia rebaudiana Bertoni is a natural alternative sweetener known for its high intensity sweetness. Stevioside, a diterpene glycoside responsible for that intense sweetness is present in the leaves of stevia. The present study aimed to examine the effects of different extraction methods and drying processes on the sweet component stevioside and assess other quality characteristics. Stevioside recovered from the leaves of stevia after extraction were 4.71%, 8.08% and 5.63% dry basis, for water, alcohol and dry infusion method, respectively, with significant differences (P<0.05) detected. Drying process had no significant effect on stevioside recovered with the highest level observed for samples subjected to a combination of alcohol extraction and freeze drying. A pattern of alcohol extraction > dry infusion extraction > water extraction in a decreasing order was observed with respect to stevioside recovery and is parallel with the levels measured in the dried extracts. Although spray drying generally yielded lower stevioside in the extracted samples, it is a more economical method in producing a powdered stevia extract since the stevioside recovered using this method was not significantly difference (P>0.05) compared to samples subjected to freeze drying. Stevia is a poor source of phenolics with values recovered ranging only from 2.06 mg GAE/g - 2.99 mg GAE/g of dried stevia leaves. The highest level was observed in alcohol extraction method and was also further reduced as affected by drying. Both powdered stevia extracts prepared by using alcohol extraction method were comparable to commercially available sample in terms of sweetness and bitter intensity as well as most physico-chemical properties.
Thesis (Master of Science in Food Science)--University of the Philippines Diliman.
Keywords: Stevia -- Philippines -- Bulacan; Natural sweeteners -- Philippines -- Bulacan